P02.07 Brain-derived circulating DNA as a biomarker for radiotherapy-induced brain damage. (19th September 2018) - Makranz, C; Zick, A; Zemmour, H; Shemer, R; Lehmann-Werman, R; Glaser, B; Maoz, M; Sapir, E; Cohen, J E; Dor, Y
Abstract: Background: Radiotherapy is a common treatment for brain metastases. However, it is commonly associated with central nervous system (CNS) toxicity, leading to functional disability. There are no biomarkers capable of detecting preclinical neurotoxicity for the purpose of early detection of radiation-induced CNS damage. Here we explore the utility of cell-free circulating DNA (cfDNA), shed from dying cells, for detection of brain cell death in the context of brain metastases. Using comparative methylome analysis we have previously identified 12 genomic loci showing brain-specific DNA methylation patterns, including markers for neurons, oligodendrocytes and astrocytes. These brain-specific methylation markers were identified in the plasma of patients suffering from multiple sclerosis, as well as traumatic and ischemic brain damage. We hypothesize that brain-derived cell-free DNA (bncfDNA) can be identified in patients suffering from brain metastases receiving radiotherapy, and can potentially be used as a biomarker to help guide treatment. Material and Methods: We recruit oncological patients treated by brain radiotherapy for brain metastases. We serially assess each patient before, during and after treatment by neurological examination. MRI studies are performed before and after radiotherapy in 2–3 months intervals. In each study visit a blood sample is collected for bncfDNA. We measure bncfDNA from serial blood samples of each patient, and correlate bncfDNA levels with clinical assessment. Results: Preliminary results on samples from 22 patients show elevation of bncfDNA in patients suffering from brain metastases (average 8501 copies/ml; range 0-112336 copies/ml) compared with an extremely low background in healthy individuals (average 6 copies/ml; range 0–33 copies/ml); p<0.0001). We observed cfDNA derived from neurons, oligodendrocytes and astrocytes, suggesting widespread damage induced by brain metastases. In the next step we studied bncDNA levels following brain radiotherapy. Preliminary results from a patient suffering from an acute central facial paralysis during radiotherapy show clinical correlation of bncfDNA levels with neurological impairment related to acute radiotoxicity. Other patients are still followed-up with bncfDNA measurement during and after end of treatment to test for early and late onset radiotoxicity effect on bncfDNA. Conclusion: BncfDNA may serve as a novel circulating biomarker for brain cell death in patients suffering from brain metastases. BncfDNA reflects brain cell death incurred by metastases, as well as damage associated with radiotherapy. Further studies of bncfDNA in the context of brain metastases and radiotherapy are needed to substantiate this idea.